Pendekatan Politik Hukum dalam Resolusi Konflik Teritorial Indonesia-Malaysia: Analisis Keterlibatan PBB dan ASEAN - Nizar, Rahadian Nizar Akbari; Dwi Hastri, Evi (UIR Law Review, 2024)
The territorial conflict between Indonesia and Malaysia has been a long-standing debate since the colonial era. One of the most contested areas between the two countries is Sipadan and Ligitan Islands on the border of the Sulu Sea. This territorial conflict arose in 1969 when Malaysia enacted the Maritime Zones Act which claimed the two islands as part of its territory. Indonesia did not recognize this claim and since then there has been tension between the two countries. This legal issue is about how the territorial conflict between Indonesia and Malaysia can be resolved through a political-legal approach involving international organizations such as the UN and ASEAN. The problem in this article is What is the political and legal strategy for resolving territorial disputes between Indonesia and Malaysia involving the UN and ASEAN Organizations? The aim of this research is to identify and analyze legal political strategies that can be used to resolve territorial disputes between Indonesia and Malaysia involving the UN Organization and ASEAN. The method used is the normative legal research method, because the normative legal research method is to analyze how the territorial conflict between Indonesia and Malaysia can be resolved through a legal political approach. The research results for this purpose are that a legal political strategy involving the UN and ASEAN Organizations can be a solution which is effective in resolving territorial disputes between Indonesia and Malaysia.